HISTRIONIC PERSONALITY DISORDER IN TENNESSEE WILLIAMS’ A STREETCAR NAMED DESIRE - Humairoh Mandani; Dian Eka Sari (LINGUA LITERA : journal of english linguistics and literature, 2019)
This research analyzed Histrionic Personality Disorder that portrayed in a drama entitled A Streetcar Named Desire. Histrionic Personality Disorder is a mental disruption where the sufferer has a big desire to be the center of attention. The problems which are discussed in this research are the symptoms of Histrionic Personality Disorder and the reasons Histrionic Personality Disorder become worse and severe. The aim of this research is to analyze deeply about Histrionic Personality Disorder issue which occur in the drama. In resolving the issue, the researcher used psychological theory by Blagov et al. The concepts which used are the symptoms of Histrionic Personality Disorder and the treatment for Histrionic Personality Disorder. This research used qualitative method in relation to the use of clear and systematic description about the phenomena being researched.